PHARMACETICO ANALYTICAL STUDY OF SHUNTHYADI TAILA AN AYURVEDIC FORMULATION - Hiremath, *Veerayya R.; Prasad, B.Srinivasa; Jadara, Prashant; lingayat, Ajit (International Journal of Ayurveda and Pharma Research, 2017)
Ayurved is treasure of medicine for various diseases & disorders. Exploring this treasure to the world in scientific manner is times need. Shunthyadi Taila in the form of Nasya has been highlighted as drug of choice for the management of Kshavathu (Sneezing). As Kshavathu is the Pradhana Lakshana of Vataja Pratishyaya. Shunthyadi Taila contains Shunthi (Zingiber officinale Rosc) Rhizome, Kushta (Saussurea lapa C.B. Clarke) Root, Pippali (Piper longum Linn) Fruit, Bilva (Aegle marmelos (Linn.) Correa ex Roxb) Root, Draksha (Vitis vinifera Linn.) Fruit and Tila (Sesamum orientale Linn) Seed oil. Shunthyadi Taila was prepared as per Standard operative procedures of Ayurvedic Pharmacopoeia of India for oil preparation. As there is no analytical standards available for Shunthyadi Taila in Ayurvedic pharmacopeia of India to check its quality. In this study, effort has been made to see results of qualitative & quantitative physcico-chemical parameters (organoleptic characters, acid value, saponification value, Iodine value, loss on drying, specific gravity and refractive index) generally applied for oil preparation as per Ayurvedic Pharmacopoeia of India. The results obtained will be the reference standards and can also be used for future studies on Shunthyadi Taila standardization.